Analisis Faktor-Faktor yang Memengaruhi Seseorang untuk Menggunakan Website LAZADA dengan Menggunakan Structured Equation Modeling (SEM) - Enrico Dimas Darmawan; Ari Kusyanti; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
E-Commerce is a type of electronic business mechanism that focuses on individual-based business transactions using the Internet as a medium of exchange of goods (Hartman, 2000). In 2016, Lazada experiencing conceded many accounts are done by people who are not responsible. The burglary victim utilize credit card to make a transaction, not just the actors also change the username and password. In the present study, the researchers conducted a test by Structural Equation Modeling (SEM) to determine the factors of what makes people to use Lazada. By combining several models of Internet Users' Information Privacy Concerns (IUIPC), User Acceptance Of Information Technology (UTAUT) as well as the added safety and confidence into this study. Constructs build the model in this study include: expectations capabilities, business expectations, the influence of social environment, facilities, risk, security and trust. Sample collection of data by using a questionnaire and analyzed by using Structural Equation Modeling (SEM). Results of the study showed that users are aware of the privacy of personal information that they provide to LAZADA. The most affected users to use Lazada factor is the trust of users towards LAZADA.